Egyptian economic indicators under the International Monetary Fund loan for the year 2016 - belbey, iman; korchi, mohamed (Journal of Research in Finance and Accounting, 2025)
This study, which adopted the analytical approach in its deductive part, came to show the repercussions of the International Monetary Fund loan for the year 2016, and the accompanying reform programs, on some indicators of the economy in Egypt, which are: domestic product, unemployment, inflation, budget deficit, and public external debt. In parallel, after the Egyptian authorities resorted to borrowing from the fund, the latter began implementing economic reform programs in order to address the imbalance in its economy, which is considered one of the repercussions of the January 2011 revolution. The results indicate a high rate of inflation, an increase in external debt, and a modest upward trend in growth rates, in addition to a slight decrease in unemployment rates. The study also recommended the need to reconsider the terms of these reforms, because of their undesirable economic and social effects. In the same context, the fund must take into account the economic and social specificity of each country, and programs must be developed that are compatible with its internal policies. On the other hand, it is appropriate for every country to adopt rationality in borrowing from abroad, and to offer appropriate alternatives.